The Wordsworth Book Of Spells - Waite, Arthur Edward (Wordsworth Editions Ltd, 1995)
This book explains the rites, mysteries and secret traditions of Witchcraft, Sorcery and Infernal Necromancy and also explores Theurgy, the White Magic which invokes beneficent spirits.
Keywords: Body, Mind & Spirit; General